Peningkatan Daya Saing UMKM Melalui Digital Branding dan Inovasi Pengemasan Produk pada UMKM di Desa Silau Rakyat, Kecamatan Sei Rampah - Bobby Hartanto; Rika Surianto Zalukhu; Suci Etri Jayanti S; Rapat Piter Sony Hutauruk; Suwadi Suwadi; Daniel Collyn; Yenni Mariani Sinurat; Ayu Zurlaini Damanik; Yenni Arfah; Kumala Vera Dewi; Cici Puspaningrum; Sri Winda Hardiyanti Damanik; Donald Frensius Pasaribu (Jurnal Pelayanan Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in rural areas still face various challenges in improving product competitiveness, particularly related to the utilization of digital technology and professional product presentation. One of the main issues encountered by MSME actors in Silau Rakyat Village is the limited understanding of digital branding and the lack of innovation in product packaging, which hinders their ability to compete effectively in the digital market. This community service program aims to enhance MSME competitiveness through training and mentoring in digital branding and product packaging innovation. The program was implemented using a participatory and applicative approach through several stages, including preparation, training, and hands-on practice. The main materials delivered focused on MSME digital branding strategies and product packaging innovation as efforts to increase product value. The results indicate an improvement in participants’ knowledge, skills, and awareness regarding the importance of brand identity, the use of digital media, and attractive and informative packaging. In addition, MSME actors began to apply more professional packaging designs and demonstrated a more adaptive attitude toward digital marketing. This community service activity is expected to support the sustainability of MSMEs and strengthen the local economy in Silau Rakyat Village.